2008
DOI: 10.1121/1.2816564
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for double acoustic windows in the dolphin, Tursiops truncatus

Abstract: In a bottlenose dolphin positions of sound receiving areas on the head surface were determined by comparing the acoustic delays from different sound-source positions. For this investigation, auditory brainstem responses (ABRs) to short tone pips were recorded and their latencies were measured at different sound source positions. After correction for the latency dependence on response amplitude, the difference in ABR latencies was adopted as being the difference of the acoustic delays. These delay differences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Anatomical studies have shown discrete fat lobes associated with the lower jaw that vary in size and shape in each species (Ketten, 1994). The mandibular fat hearing hypothesis is supported by physiological data, particularly for the concept of an additional pathway near the bulla, which preferentially receives lower frequency sounds (Popov et al, 2008).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Anatomical studies have shown discrete fat lobes associated with the lower jaw that vary in size and shape in each species (Ketten, 1994). The mandibular fat hearing hypothesis is supported by physiological data, particularly for the concept of an additional pathway near the bulla, which preferentially receives lower frequency sounds (Popov et al, 2008).…”
Section: Introductionmentioning
confidence: 63%
“…While these data may not conclusively support a double acoustic window for the finless porpoise, they do indicate these porpoises hear low frequencies better from the side and higher frequencies better at anterior positions; and at least suggest the need for further investigations. Such a double-acoustic window has been proposed for the bottlenose dolphin (Popov et al, 2008). The porpoise's frequency-dependent general regions of low and high frequency sensitivity are less specific than in the bottlenose dolphin, which shows considerable (near 40 dB) differences across the head (Møhl et al, 1999).…”
Section: Relative Hearingmentioning
confidence: 99%
“…As this field of study advances, the evidence for how and where sounds are received suggests that this process is more complex than originally conceived (Møhl et al 1999;Popov et al, 2008;Cranford et al, 2008a,b). Regardless of the exact mechanism(s), it is clear that the hollow posterior portion of the mandibles is an integral part of sound reception in odontocetes.…”
Section: Introductionmentioning
confidence: 99%
“…The signals were monitored using an oscilloscope (Tektronix TDS1002C, Beaverton, OR, USA) before being projected through a Reson TC-4040 hydrophone (Reson, Slangerup, Denmark), which was positioned at a distance of ~2m and a depth of 0.5m in front of the subject's 'acoustic windows' along the body axis. The 'acoustic windows' are located at the lower jaw area of the subject, through which sound is assumed to travel to the inner ear (Norris, 1968;Popov et al, 2008). Sound pressure levels (SPLs, dB re.…”
Section: Hearing Measurementmentioning
confidence: 99%
“…On the same day, the dolphin was transported to the rescue centre of the Pearl River Estuary Chinese White Dolphin National Nature Reserve, Zhuhai, China (Fig.1B) (C)The dolphin was positioned in a stretcher at the water surface while wearing electroencephalography (EEG) electrodes attached to the skin by soft silicone suction cups. The sound projector was positioned ~2m from the animal's 'acoustic windows', where the sound is assumed to travel to the animal's inner ear (Norris, 1968;Popov et al, 2008).…”
Section: Subjectmentioning
confidence: 99%